The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10551-020-04655-6
|View full text |Cite
|
Sign up to set email alerts
|

Fear and Violence as Organizational Strategies: The Possibility of a Derridean Lens to Analyze Extra-judicial Police Violence

Abstract: Governments and majoritarian political formations often present police violence as nationalist media spectacles, which marginalize the rights of the accused and normalize the discourse of majoritarian nationalism. In this study, we explore the public discourse of how the State and political actors repeatedly labeled a college-going student Ishrat Jahan, who died in a stage-managed police killing in India in 2004, as a terrorist. We draw from Derrida’s ethics of unconditional hospitality to show that while poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…As Douglas (1966 [2002]) argues, “the pollution [becomes] a doubly wicked object of reprobation, first because he crossed the line and second because he endangered others” (as cited in Varman et al, 2021: 648). This is reminiscent of the politics of fear and violence that Jagannathan et al (2022) and Prasad (2020) highlight in their studies of state brutality against Muslims in contemporary India.…”
Section: Discussionmentioning
confidence: 96%
“…As Douglas (1966 [2002]) argues, “the pollution [becomes] a doubly wicked object of reprobation, first because he crossed the line and second because he endangered others” (as cited in Varman et al, 2021: 648). This is reminiscent of the politics of fear and violence that Jagannathan et al (2022) and Prasad (2020) highlight in their studies of state brutality against Muslims in contemporary India.…”
Section: Discussionmentioning
confidence: 96%
“…Researchers have shown that Indian security forces "identify with structures of majoritarian nationalism to enact violence. " 32 The 2019 ruling by India's Supreme Court in favor of Hindu nationalists who destroyed the 16 th century Babri Mosque in 1992 is the culmination of BJP's effort to chip away at the rights of Muslims in the judiciary, and thus reaffirming their status as second-class citizens in a supposedly secular democratic country. 33 This rising animosity and violence towards Muslims by the Hindu majority population reached a zenith over six bloody days in New Delhi during February 23-29, 2020, when more than 50 Muslims were murdered after a BJP leader gave a speech urging supporters to attack anti-CAA protesters.…”
Section: Ami Vitale / Getty Imagesmentioning
confidence: 99%